A new species of Odontothrips Amyot & Serville (Thysanoptera, Thripidae) from Japan - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2021)
Odontothrips kudoi sp. n. is described from Japan and details of Japanese distribution of O. biuncus John is recorded. Moreover, O. loti (Haliday) is excluded from the Japanese fauna.